2018
DOI: 10.3390/f9110697
|View full text |Cite
|
Sign up to set email alerts
|

The Use of qPCR Reveals a High Frequency of Phytophthora quercina in Two Spanish Holm Oak Areas

Abstract: The struggling Spanish holm oak woodland situation associated with Phytophthora root rot has been studied for a long time. Phytophthora cinnamomi is considered the main, but not the only species responsible for the decline scenario. This study verifies the presence and/or detection of Phytophthora species in two holm oak areas of Spain (southwestern "dehesas" and northeastern woodland) using different isolation and detection approaches. Direct isolation and baiting methods in declining and non-declining holm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 60 publications
6
24
0
Order By: Relevance
“…Most of the Phytophthora taxa found in our samples were also recorded in a soil analysis in the search for oomycete in natural Q. ilex forests of eastern Spain 29 , where P. psychrophila and P. quercina were the most-relevant taxa, and also a qPCR survey showed P. quercina abundance in dehesas of Extremadura 30 ; P. psychrophila and P. quercina appeared, respectively, as the third- and fourth-most-abundant oomycete species in our study. Both taxa have been confirmed as Q. ilex root pathogens, causing root rot and tree death 74 .…”
Section: Discussionsupporting
confidence: 62%
“…Most of the Phytophthora taxa found in our samples were also recorded in a soil analysis in the search for oomycete in natural Q. ilex forests of eastern Spain 29 , where P. psychrophila and P. quercina were the most-relevant taxa, and also a qPCR survey showed P. quercina abundance in dehesas of Extremadura 30 ; P. psychrophila and P. quercina appeared, respectively, as the third- and fourth-most-abundant oomycete species in our study. Both taxa have been confirmed as Q. ilex root pathogens, causing root rot and tree death 74 .…”
Section: Discussionsupporting
confidence: 62%
“…The weather conditions of the Extremadura region were more favorable for Phytophthora development in 2013 than in 2012, since in 2012 Extremadura received less precipitation than in 2013, as reported in 2018 by Mora-Sala et al [48]. Redondo et al [57] state that there is a decrease in the diversity of terrestrial Phytophthora communities when temperature and precipitation decreases, precipitation being the main driving factor, except for clades 2 and 8, in which temperature was more conditioning.…”
Section: Discussionmentioning
confidence: 86%
“…Soil and roots samples were conserved at 5 • C until DNA extraction was performed. Baiting with leaflets of Rhododendron sp., Viburnum tinus L, Quercus ilex L, Quercus suber L, Ceratonia siliqua L. and/or Dianthus caryophyllus L. petals was performed as described in a previous study [48], and the vegetal material from the baitings was conserved at -80 • C until DNA extraction.…”
Section: Study Site and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that visual surveying was more efficient than bark shifting. Meanwhile, Mora-Sala et al [22] demonstrated the efficiency of qPCR approaches to determine the presence and distribution of Phytophthora sp. in holm oak areas.…”
Section: Papers In This Issuementioning
confidence: 99%